STRATEGI BERTAHAN HIDUP PEREMPUAN PENANGGUNG JAWAB KELUARGA: STUDI KEPALA KELUARGA PENGANGGURAN DI KABUPATEN CIREBON - Farhan, Mochammad; Musahwi, Musahwi (JURNAL KELUARGA SEHAT SEJAHTERA, 2025)
This study describes the survival strategies of women family caregivers in Perbutulan Village, Cirebon Regency, especially unemployed family heads. Women who are responsible for families with unemployed heads of households face double pressure; acting not only as the manager of the house but also as the main breadwinner, even though they often get uncertain income. This research uses qualitative methods through in-depth interviews, observation, and document collection. The results showed that women family caregivers use various strategies, including active strategies (optimizing the potential of their family and surrounding environment, such as selling, farming, and raising livestock), passive strategies (managing and reducing family expenses), and network strategies (utilizing social support and relationships through participation in community activities). The findings of this study are expected to illustrate and provide an understanding of the ways of survival for women who are responsible for the family, as well as a reference for future research in this area.